ANALISIS CRITICAL SUCCESS FACTORS DALAM MENILAI KINERJA GUNA MENCAPAI KEUNGGULAN BERSAING - Tawakal, Abdillah; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research was to analyze the critical success factors with TOWS method as performance assessment in achieving competitive advantage. The research method has been carried out by using qualitative methods and descriptive analysis. Performance measurement using balance scorecard method on the customer perspective. Based on the result of the analysis and the discussion it indicates that the threatsto the institution are the demands of society, the lack of public awareness.The opportunities are strategic place, public demand for qualified Islamic education, the availability of boarding school learning programs, full day school and takhasus. The weaknessesare the lack of comprehension of new teachers to the indicator of vision, mission and the goals of the school and also the enhancementof the cost of the program. The strenghtsare the experience, the totality of educating children with a strong faith by using integral education, the ability in marketing and competent teachers in teaching students.Based on the results of this study concluded that by analyzing the critical success factors by the method of TOWS in the performance appraisal process can create competitive advantage for the institution strategy.Keywords : CSF, Customer Perspective, Competitive Advantage